Case Study of Sound Production and Dolphin Behavior in Waters - Rita Puspita Heryani (Faculty of Fisheries and Marine, Universitas Riau, 2022)
Dolphins belong to the Cetacean Order and are members of the Odontocetes with physical characteristics and the sound signals they emit. This fish lives in the sea and is one of the rare animals. The preparation of this scientific article was carried out in May 2021 using a descriptive analysis based on a literature review using secondary data as a source of information. The sound frequency range with the highest intensity value is 32 dB in the frequency range of 14 - 16 kHz.